GeneID in Drosophila - Parra, Genís; Blanco, Enrique; Guigó, Roderic (Genome Research, 2000)
GeneID is a program to predict genes in anonymous genomic sequences designed with a hierarchical structure. In the first step, splice sites, and start and stop codons are predicted and scored along the sequence using position weight matrices (PWMs). In the second step, exons are built from the sites. Exons are scored as the sum of the scores of the defining sites, plus the log-likelihood ratio of a Markov model for coding DNA. In the last step, from the set of predicted exons, the gene structure is assembled, maximizing the sum of the scores of the assembled exons. In this paper we describe the obtention of PWMs for sites, and the Markov model of coding DNA inDrosophila melanogaster. We also compare other models of coding DNA with the Markov model. Finally, we present and discuss the results obtained when GeneID is used to predict genes in the Adh region. These results show that the accuracy ofGeneID predictions compares currently with that of other existing tools but that GeneID is likely to be more efficient in terms of speed and memory usage. GeneID is available at http://www1.imim.es/∼eblanco/GeneId.
10.1101/gr.10.4.511